2016
DOI: 10.1093/jhps/hnv078
|View full text |Cite
|
Sign up to set email alerts
|

Patient reported outcomes for patients who returned to sport compared with those who did not after hip arthroscopy: minimum 2-year follow-up

Abstract: Previous studies assessed elite athletes’ return to sport (RTS) after hip arthroscopy, but few investigated a cohort including athletes from all levels of sport. This study compared athletes who returned to sport to those who did not, based on four patient-reported outcome (PRO) scores, including the Hip Outcome Score—Sports Specific Subscale (HOS-SSS). Between September 2008 and April 2012, hip arthroscopies were performed on 157 patients (168 hips) who reported playing a sport preoperatively and indicated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
34
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 17 publications
(25 reference statements)
2
34
0
Order By: Relevance
“…The outcomes of this study are comparable to previously reported studies with significant functional improvement as well as high return to sport/activity. [4][5][6][7]13,14,[18][19][20] This studies results suggest that accelerated weight bearing and early ROM can assist in attaining positive outcomes in terms of early improvements in rehabilitation while minimizing potential adverse effects, a concept that is supported in the literature. 18 Likewise, there were no observed failures related to early weight bearing to include catastrophic failures such as femoral neck fracture or hip instability.…”
Section: Discussionmentioning
confidence: 60%
“…The outcomes of this study are comparable to previously reported studies with significant functional improvement as well as high return to sport/activity. [4][5][6][7]13,14,[18][19][20] This studies results suggest that accelerated weight bearing and early ROM can assist in attaining positive outcomes in terms of early improvements in rehabilitation while minimizing potential adverse effects, a concept that is supported in the literature. 18 Likewise, there were no observed failures related to early weight bearing to include catastrophic failures such as femoral neck fracture or hip instability.…”
Section: Discussionmentioning
confidence: 60%
“…(32,35) Return to sport appears to be highly influenced by factors such as self-motivation, aging, pain, encouragement, and adaptation to physical limitations. (38,39) These factors as well as monetary incentives and the limited window to play at the elite level motivate professional athletes to return to play. In a recent systematic review, Casartelli et al reported a 87% return to sport rate in both competitive and recreational athletes.…”
Section: Discussionmentioning
confidence: 99%
“…With the development of this technique, associated with the discovery of predisposing factors to various arthropathies, restoration of function through minimally invasive procedures, essentially eliminating lesions and helping patients return to normal activities, was even more safe and effective [18].…”
Section: Arthroscopymentioning
confidence: 99%
“…Arthroscopy of hip-like joints offers minimally invasive surgery for procedures that would require hip dislocation, a more complicated technique. In this joint, the most commonly treated pathologies are femoroacetabular impacts, which are closely associated with demanding activities in hip flexion and internal rotation, common in sports such as golf, baseball, ice hockey, and soccer [7,18,43,54].…”
Section: Arthroscopymentioning
confidence: 99%